Eighteen‐year follow‐up of hyperopic photorefractive keratectomy. Issue 2 (February 2016) - Wagh, Vijay K.; Dave, Reena; O'Brart, David P.S.; Lim, Wei S.; Patel, Parul; Tam, Connan; Lee, Jennifer; Marshall, John
Abstract : Purpose : To investigate the long‐term efficacy of hyperopic photorefractive keratectomy (PRK). Setting : University Hospital, London, United Kingdom. Design : Prospective case series. Methods : Patients with a follow‐up of 18 years ± 0.7 (SD) attended for examination. All had spherical corrections with a 6.5 mm optical zone and 1.5 mm blend zone. Results : Twenty‐five patients (45 eyes) were included. The mean preoperative spherical equivalent (SE) refractive error was +4.11 ± 1.8 diopters (D) (range +1.125 to +7.25 D). Between 1 year and 18 years, in eyes that had no cataract surgery (n = 34), there was a +1.14 ± 1.48 D increase in the mean SE ( P < .0002). The increase between 7.5 years and 18.0 years did not reach clinical significance ( P = .1). Uncorrected distance visual acuity improved at 18 years ( P < .02). Corrected distance visual acuity (CDVA) was reduced ( P < .001). The efficacy index was 0.47, and the safety index was 0.83. Six eyes (18%) lost 2 lines of CDVA, of which 4 eyes had preexisting cataract. Keratometry remained stable between 1 year and 18 years ( P = .2). Forty percent still had traces of peripheral haze, and 4 (9%) had Salzmann‐like changes. Eleven eyes (24%) had cataract surgery and 4 (9%) had laser iridotomy. There was no evidence of ectasia. Conclusions : Hyperopic PRK showed an increase in hyperopic SE between 1.0 year and 7.5 years but was generally stable thereafter. The efficacy was limited. Peripheral haze was evident in 40% of cases with Salzmann‐like changes in some. Ocular comorbidity in relationship to cataract was common and reduced CDVA. Financial Disclosure : Dr. Marshall was a consultant to Summit Technology, Inc. No author has a financial or proprietary interest in any material or method mentioned.